Laparoscopic Repair of Foramen of Winslow Hernia - Garg, Shailesh; Flumeri-Perez, Giovanni; Perveen, Shabana; DeNoto, George (International Journal of Angiology, 2016)
Foramen of Winslow hernia is a rare surgical entity with very few reported cases in literature. Preoperative diagnosis used to be difficult but with emerging computed tomography technology, diagnosing this internal abdominal hernia has become easier.We present an unusual case report of foramen of Winslow hernia in a 77-year-old patient who presented with severe abdominal pain. The patient underwent laparoscopic repair of the hernia and recovered well postoperatively.This presentation of symptoms in a 77-year-old male is unusual and laparoscopic management of foramen of Winslow hernia presents an interesting and challenging management scenario.
Keywords: foramen of Winslow hernia; epiploic foramen; epiploic hernia; hernia into lesser sac; internal abdominal hernia